Postawy użytkowników towarowych gospodarstw rolnych regionu opolskiego wobec nowej równowagi przestrzeni wiejskiej - Bisaga, Anna (The bases of the users of farms in Opole region in the face of new special balance of rural area, 2007)
The balanced development of European agriculture presupposes improvement of natural environment and landscape through multifunctional farming, subject to numerous norms, which will guarantee safe food and observance of good agricultural practice. Empirical research among farmers in Opole region shows that the entering of EU strengthened the need for leaming new technologies of production and use of economy, which makes people look for new agricultural production - mainly of energy raw materials. The pressure of norms is not too strong for the time being. Although farmers are afraid of soil ąuality assessment.
Prace Naukowe Akademii Ekonomicznej we Wrocławiu; 2007; nr 1190, s. 346-355